Postoperative pain management following laparoscopic cholecystectomy-non-opioid approaches: a review - Hoda Mohamed Bayoumi; Doaa Hamed Abdelaziz; Nouran Omar El Said; Sherif Boraii; Ehab Rasmy Bendas (SpringerOpen, 2024)
Abstract Background Gallstone disease with its consequences is a common clinical issue that may necessitate surgical removal. In comparison with traditional open procedures, laparoscopic cholecystectomy (LC) remains the mainstay treatment for symptomatic gallstone disease and can lead to a shorter recovery period, and a shorter hospital stay; yet, severe abdominal and shoulder pain may be experienced. Main body Novel drugs and technology for acute and chronic pain management following LC have been studied to improve patient care. The review discusses innovative pain management strategies with non-opioid approaches for laparoscopic surgery, with an emphasis on ensuring speedy and safe recovery. Conclusion The key findings state that IV paracetamol is a necessary part of multimodal postoperative pain management. There were several pharmacological interventions found to be effective in pain control: magnesium sulfate and dexamethasone showed anti-inflammatory benefits; ondansetron provided analgesic effects; gabapentinoids and alpha-2-agonists reduced central sensitization; local anesthetics offered targeted pain relief; antidepressants addressed neuropathic pain; NSAIDs proved effective for inflammatory pain. Similarly, non-pharmacological approaches, and emerging technologies, also contributed to the management of post-LC pain underscoring the need for a comprehensive approach to its management. More rigorous research is needed to guide pain management after LC. Future studies should compare multiple treatments simultaneously and involve larger patient groups. This approach will help identify optimal pain control strategies. It will also provide clearer insights into the safety and efficacy of various pain medications under comparable clinical conditions.